PENDEKATAN SAINTIFIK DALAM PEMBELAJARANPENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SD NEGERI 3 KALISONGO - Sunarto (JIPI (Jurnal Ilmiah Pendidikan Islam), 2023)
SD Neger 3 Kalisongo is one of the public elementary schools that has carried out learning using a scientific approach. Moreover, one of the teachers of Islamic Religious Education at SD Neger 3 Kalisongo is one of the scientific learning trainers who has a good understanding and mastery of this matter. The main problems of this research are 1) How is the implementation of the scientific approach in learning Islamic Religious Education and Characteristics at SD Negeri 3 Kalisongo?; 2) What are the advantages obtained by teachers with a scientific approach in learning Islamic Religious Education and Moral Character at SD Negeri 3 Kalisongo?; 3) What are the problems faced by teachers with a scientific approach in learning Islamic Religious Education and Character at SD Negeri 3 Kalisongo? The type of research in this study is qualitative, while based on its objectives, the type of research that will be used is descriptive research. Thus the type of research that will be used in this study is a type of qualitative descriptive research. Learning Islamic Religious Education and Character with a scientific approach begins with observing activities, followed by asking questions, gathering information, associating, and communicating results.